Deux questions à propos de l'implication mutuelle de l'esprit critique et de la laïcité dans l'appréhension républicaine de l'éducation morale et civique - Roger Monjo
In the republican understanding of the missions assigned to school, both concepts of secularism and critical thinking are traditionally associated to each other: the development of critical thinking can only happen in an educational institution obeying to the principle of secularism and vice versa; the development of critical thinking allows the reinforcement and strengthening of the legitimacy of this principle. In this article, we question the prerequisites of this mutual implication: in what sense is a critical approach only conceivable in a secular context? Why does secularism appear as a necessary consequence of the development of critical thinking? Among those prerequisites the traditional oppositions between belief and knowledge, faith and rationality, religion and science will be put into relief.